2010
DOI: 10.1007/s00213-010-2041-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characterization of tryptophan hydroxylase 2-specific cortical serotonergic fibers and dorsal raphe neuronal cell bodies after MDMA treatment in rat

Abstract: Rationale 3,4-Methylenedioxymethamphetamine (MDMA, "ecstasy") is a widely used recreational drug known to cause selective long-term serotonergic damage.Objectives The aim of this study was to characterize the ultrastructure of serotonergic pericarya and proximal neurites in the dorsal raphe nucleus as well as the ultrastructure of serotonergic axons in the frontal cortex of adolescent Dark Agouti rats 3 days after treatment with 15 mg/kg i.p. MDMA.Methods Light microscopic immunohistochemistry and pre-embeddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 61 publications
5
8
0
Order By: Relevance
“…The changes in the DR region were mild in line with our previous results suggesting that MDMA-caused damage to these neurons are restricted to serotonergic axon terminals instead of neuronal cell bodies directly [71]. The caspase activation gene set significantly changed in the present study was not supported by individual genes, or other gene sets related to apoptotical processes.…”
Section: Discussionsupporting
confidence: 88%
“…The changes in the DR region were mild in line with our previous results suggesting that MDMA-caused damage to these neurons are restricted to serotonergic axon terminals instead of neuronal cell bodies directly [71]. The caspase activation gene set significantly changed in the present study was not supported by individual genes, or other gene sets related to apoptotical processes.…”
Section: Discussionsupporting
confidence: 88%
“…There were no swollen axons seen in the more proximal portions of the axonal trajectory including those that pass through the linear nucleus of the raphe, the posterior hypothalamus and the more caudal portions of the MFB (data not shown). This pattern is consistent with the early stages of retrograde axonal degeneration and is congruent with a well-established literature on amphetamine-induced degeneration of serotonin axons in rats, which has gone to great lengths to demonstrate the hallmarks of degeneration including swollen, irregular axons (Molliver et al, 1990) and has used immuno-electron microscopy to show amphetamine-evoked destruction of microtubules and degenerated mitochondria in such axons (Adori et al, 1980). Figure 2 shows representative images taken 1 week after PCA or saline treatment, starting with the serotonergic cell bodies of origin in the dorsal raphe nucleus and continuing with their long C-shaped projection through the MFB and ending in the occipital cortex.…”
Section: Resultssupporting
confidence: 87%
“…In this regard, it has been shown that MDMA administration does not lead to ultrastructural alteration in the serotonergic dorsal raphe cell bodies and in their proximal neurites but causes impairment in cortical serotonergic axons. In these, the main ultrastructural alteration is the destruction of microtubules although a smaller portion of these axons probably undergoes an irreversible damage [196]. These data support the clinical findings reported by Kish et al .…”
Section: Neuroadaptation Vs Neurotoxicitysupporting
confidence: 81%